Investigation on the Effect of Work Flexibility Policy on Job Satisfaction and Performance of Millennial Generation Employees in Start-UP Companies in DKI Jakarta - Susanto, Andi Heru; Kramadibrata, Budi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine the effect of job flexibility policies on job satisfaction and millennial generation employee performance in start-up companies in DKI Jakarta. This research uses a quantitative approach with survey methods. The population of the study, namely start-ups in DKI Jakarta, amounted to 1256. The sampling technique used is multistage random sampling. The determination of the final sample size to be used as respondents refers to the Generic Formula, and a total sample of 294 employees is obtained. The data analysis used is multiple regression analysis. The results of data analysis show that there is a positive and significant influence of work flexibility on the performance of millennial generation employees in start-up companies in DKI Jakarta by 62.6%. Affected by the positive and significant influence of job satisfaction on the performance of millennial generation employees in start-up companies in DKI Jakarta by 42.3%. There is a simultaneous influence (together) between the implementation of work flexibility and job satisfaction on the performance of millennial generation employees in start-up companies in DKI Jakarta by 62.6%.